Development of State-Owned Enterprises Subject to Private Law in the Aeronautical Maintenance Sector in the Peruvian Navy - Angulo Rebaza, Cesar Adolfo (2021)
The investigation consisted of demonstrating methodologically that it is possible to develop the aeronautical maintenance industry within the Peruvian Navy (MGP) by means of a novel undertaking in the field of business management within the MGP, that is to say, the design of a state-owned enterprise (SOE) subject to private law that allows the growth of the aeronautical sector within a legal framework that helps achieve a balance between efficiency and effectiveness. The analysis of the current situation of aeronautical maintenance in the MGP identified that it is not taking advantage of potentialities in human and certified materials (capability). Therefore, the application of administrative theories will make it possible to optimize the management process, generating greater competitiveness and profitability. The correlational descriptive method was used through the application of surveys and its results validated the proposal, as well as its viability as a decentralized and specialized agency of SIMA Peru. This scenario would contribute to meeting the aeronautical needs of the MGP in maintenance management practices, organizational culture, TMA capability, profitability, commercial agility, technology and quality assurance, which have a significant relationship with operational performance, that also impacts the development of aeronautical technology in the country.